Pola Komunikasi Wartawan Istana dalam Membuat Berita - Erik Purnama Putra (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
This research is aimed to describe the communication patterns of the Presidential Palace journalists when they want to get and write news. The journalists who were assigned in Predidential Palace must come from different media. There were dozens of journalists from various media who were assigned in the Presidential Palace. However, the Presidential Palace journalists had been seen as prestigious because they were assigned in important posts. This research used a constructivist paradigm approach. The dats collection was carried out by observing and interviewing the journalists in the field. In writing news, the Presidential Palace journalists were also bounded by the agreement between the journalists from various media who are assigned to the Presidential Palace. The results showed that Presidential Palace journalists shared news with each other and established communication, so that everyone could get news. Among the Presidential Palace journalists, sharing the results of interviews was common. This condition made the news that appeared in various media, especially online, to be almost the same, even though the angle chosen is different. They also did not know the practice of breaking into or looking for exclusive news, because if that happened, the access to information could be closed.